Research Trend on E-democracy Publications: A Bibliometric Analysis - Gusti Chairunnisa Adinda Syahputri; Dedik Fitra Suhermanto; Ali Roziqin; Binti Azizatun Nafi'ah (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
The e-democracy system that continues to change and develop every year is an exciting topic to continue to be studied. Since the massive development of information and communication technology, research related to e-democracy is now a trend carried out by scholars. The article aims to evaluate the e-democracy research trend through bibliometric analysis techniques in two decades (2001-2020). This article uses a bibliometric analysis with applied VOSviewer to provide researchers with describing data and Gephy software to map network classification. Countries in Europe and the Americas dominate the research and implementation of the e-democracy system through a smaller approach, namely, e-government. This article found nine main clusters of 306 articles that have been coming from different countries, affiliates, and authors. This clusterization mapping was helpful for future researchers in developing and discussing their research on the study of e-democracy.